Analysis of the application of Sharia principles in student savings products - Erlina, Erlina; Yanti, Nursantri; Harianto, Budi (LPMP Imperium, 2024)
This research aims to determine the application of Sharia principles to student savings at Bank Syariah Indonesia KCP Simpang Limun and to explain the application of the contracts used in student savings. This research includes field research with a qualitative approach. In terms of its nature, the research is descriptive and analytical. Data was obtained using primary and secondary data by taking samples from staff employees of Bank Syariah, which were taken from interviews regarding student savings. The research results show that Islamic Sharia has implemented student savings at this bank. However, the bank still needs to carry out a less active and effective level of promotion, so student savings are still relatively low. Bank staff must strive for more active and effective marketing in increasing awareness about the benefits of student savings products to encourage more potential customers. Public interest statements As banks adopt these strategies to improve customer satisfaction, the public can expect increased competition in the banking sector. This competition may lead to better services, lower fees, and more innovative products, benefiting consumers. Article Info: Received 6/13/2024 | Revised: 9/28/2024 | Accepted: 9/23/2024 | Online First 9/29/2024